THE PROCESS OF DIGITAL TRANSFORMATION IN ENTERPRISES: METHODS OF INTEGRATION OF DIGITAL MARKETING TOOLS AND EFFECTIVENESS ASSESSMENT (Marketing Journal, 2025)
This article analyzes the process of digital transformation in enterprises, the integration of digital marketing tools, and methods for evaluating their effectiveness. The impact of modern digital technologies on business models, production processes, and marketing strategies has been studied. Additionally, the significance of digital marketing tools in the service sector, the development of the digital economy, and the strategic importance of digital transformation processes in enterprises are highlighted. The process of implementing digital marketing strategies in enterprises and methods for assessing effectiveness —based on indicators such as ROI, CPC, CAC, and CR—have been analyzed. Furthermore, government programs aimed at developing the digital economy a nd supporting digital transformation in Uzbekistan and their impact on the economy have been covered.
Keywords: digital transformation; digital marketing; digital economy; marketing tools; digital technologies; Big Data; IoT; ROI; CPC; CAC; CR; digital platform; digital business models; competitiveness; automation; digitization; e - commerce; online marketing; digita l strategies